Organizational-Economic Directions of the Effective Use of Supply Chain Strategy in Rural Territories of Kazakhstan - A. Kaliyev, Gani; I. Sabirova, Alla; U. Akimbekova, Galiya; A. Glushan, Lyudmila; N. Zhildikbaeva, Aizhan (ExcelingTech, 2019)
The article discusses the issues of creating a solid fodder basis for keeping livestock in the personal subsidiary farm of the rural population based on supply chain strategy. The analysis of the use of pastures on fixed lands of settlements has been conducted based on the example of five regions of Kazakhstan and a number of rural districts. A huge shortage of pastures in the territories of rural settlements and a discrepancy between the livestock population of the households and the level of their feed supply have been revealed. The assessment of the current regulatory and legislative framework and prospects for the organizational and economic use of these territories is presented. The necessity of regulating the use of pastures through the application of standards for limiting the livestock management per one household, the system of pasture rotation and radical improvement of pastures, allocation of additional areas at the expense of reserve lands, development of cooperation have been justified.